2001
DOI: 10.1136/tc.10.1.e1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of smoking on the roof of the world

Abstract: Conclusion-Cigarette smoking is a major public health problem in this high mountain community of Pakistan, particularly among the male population, the majority of whom begin to smoke quite early in life. A comprehensive tobacco control eVort incorporated into the existing community based health infrastructure is needed. (Tobacco Control 2001;10:e1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
3
10
1
Order By: Relevance
“…However, our study period was short and involved physiological changes in body size consequently, further evaluation is required. These results were independent of factors that have been associated with high blood pressure, such as tobacco consumption (Shah et al, 2001), puberty (Shankar et al, 2005), physical activity (Dencker et al, 2008), and height (a variable reflecting an adjustment for ethnic variations) (Chiolero et al, 2007a). Still, our study has limitations, such as not having included other life history variables such as birth weight and diet, and in particular salt consumption (He et al, 2008), which has been shown to be involved in increased blood pressure in children and adolescents (Chiolero et al, 2007a).…”
Section: Discussionmentioning
confidence: 57%
“…However, our study period was short and involved physiological changes in body size consequently, further evaluation is required. These results were independent of factors that have been associated with high blood pressure, such as tobacco consumption (Shah et al, 2001), puberty (Shankar et al, 2005), physical activity (Dencker et al, 2008), and height (a variable reflecting an adjustment for ethnic variations) (Chiolero et al, 2007a). Still, our study has limitations, such as not having included other life history variables such as birth weight and diet, and in particular salt consumption (He et al, 2008), which has been shown to be involved in increased blood pressure in children and adolescents (Chiolero et al, 2007a).…”
Section: Discussionmentioning
confidence: 57%
“…Current smokers were defined as those: (i) "smoking at least one cigarette each day" 19,35 ; (ii) "smoking one or more cigarettes daily for 6 months or more before the survey" 36,37 ; (iii) "smoking tobacco products at the time of the survey" 15,38,39,40,41,42 ; (iv) "having smoked at least 100 cigarettes in one's lifetime and currently smoke every day or some days or continue to smoke regularly or were still smoking daily at the time of the interview" 10,11,12,14,17,26,43,44,45,46,47 49,50 ; (iii) ever smokers -"more than 100 cigarettes in their lifetime" 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Occupation was classified as follows: Group I – housewives, students, unemployed; Group II – farmers, unskilled workers; Group III – businessmen, skilled workers; Group IV – government employees. Further details about methods have been mentioned elsewhere (Shah et al. 2001a,b).…”
Section: Methodsmentioning
confidence: 99%